Editorial: Research and university - El Director (2012)
This 12th issue of the IECOS Magazine presents new angles from which we can observe some symptoms that seem to alert us to the process of flagrant deterioration and wear that the Peruvian university has been experiencing since the mid-sixteenth century, when the first university in the American continent was created in Lima, more than one hundred years before the creation of Harvard University. Nevertheless, the principles that supported the independence of the United States of America appeared on the Latin American horizon together with the teachings of the French Revolution and the new liberal and humanist philosophy that consecrated equality and fraternity among men, and the development of science and technology (which were favored by the maturation process of mathematics, physics and chemistry), within the framework of Christian morality that with the advent of democracy would become citizens with recognized rights to elect and be elected.